Evaluation of the SAMe-TT2R2 score to predict the quality of anticoagulation control in patients after mitral valve replacement - Li, Yilin; Gao, Yang; Hu, Qiuming; Meng, Xu; Li, Shubin (Frontiers in Surgery, 2025)
BackgroundThis study aimed to evaluate the role of the SAMe-TT2R2 score in the prediction of anticoagulation control after mechanical mitral valve replacement.Methods and resultsWe retrospectively reviewed clinical data of 160 patients who received mechanical mitral valve replacement at Beijing Anzhen Hospital from January to December 2013. Collected data included the patient's general information and any history of medication, smoking, post-operative embolism due to anticoagulant, bleeding complications, and death information. In the SAMe-TT2R2 score results, the lowest score was 2 points (5.6%), and the highest score was 7 points (0.6%). The number of people with 4 points was the largest (69 people, 43.1%). When the cut-off value of the SAMe-TT2R2 score was set to ≥4, the sensitivity and specificity of predicting Time in Therapeutic Range (TTR) ≥65% were 69.8% and 93.1%, respectively. The Youden index was 0.629. If the cut-off value of the SAMe-TT2R2 score was set to ≤4, the sensitivity and specificity of predicting TTR ≥65% were 93.0% and 44.1%, respectively, and the Youden index was 0.371. The Receiver Operator Characteristic (ROC) curve evaluates the predictive power of the SAMe-TT2R2 score for TTR ≥65%. The figure showed that when the cut-off point was ≥4, the best combination of sensitivity and specificity was shown (69.8% and 93.1%, respectively). The Area Under the Curve (AUC) was 0.854.ConclusionsAfter mechanical mitral valve replacement, the SAMe-TT2R2 model can effectively predict the TTR level during the course of oral warfarin anticoagulation therapy. The SAMe-TT2R2 score ≥4 can predict TTR <65%.